2001
DOI: 10.1080/080352501317130272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of severity of congenital hypothyroidism and adequacy of treatment on school achievement in young adolescents: a population-based cohort study

Abstract: Careful follow-up of the adequacy of treatment is required throughout childhood, to reduce the risk of school delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 30 publications
(65 reference statements)
0
8
0
1
Order By: Relevance
“…It was remarked that the neurological outcome is related also to the treatment [3, 5, 18, 19, 30], and that the foetal hypothyroidism plays an important role in the brain development which can be just partially supplied by the later medical treatment [5, 15, 29, 30]. Our athyreotic patients were significantly more often B– than B+, confirming the previous findings, and had a higher, but not statistically significant, rate of low T4 at diagnosis, but reasonably the lack of significance could be explained by the sample size and/or the choice of an inappropriate cut-off to define the biochemical degree of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was remarked that the neurological outcome is related also to the treatment [3, 5, 18, 19, 30], and that the foetal hypothyroidism plays an important role in the brain development which can be just partially supplied by the later medical treatment [5, 15, 29, 30]. Our athyreotic patients were significantly more often B– than B+, confirming the previous findings, and had a higher, but not statistically significant, rate of low T4 at diagnosis, but reasonably the lack of significance could be explained by the sample size and/or the choice of an inappropriate cut-off to define the biochemical degree of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work claiming that any IQ deficit could be reversed by early, high-dose, T4 treatment was, in retrospect, over-optimistic being based on small numbers of patients aged only 18 months (33). However, postnatal management and compliance with treatment have been shown to affect outcome, a French cohort study of 682 patients born between 1979 and 1985 showing that inadequate treatment in childhood was an independent factor in school delay (34). …”
Section: Introductionmentioning
confidence: 99%
“…The assessment of both the impact of disease severity and the degree to which this can be offset by postnatal management is difficult and requires long-term follow-up into adulthood, by which time practice is bound to have changed. Although much can be learned from the admirable French cohort studies of Léger et al (32,34), there is a dearth of large-scale, prospective studies in which children have been systematically treated according to agreed protocols. There is an urgent need in Europe for new consensus guidelines to update previous ESPE recommendations (49).…”
Section: Introductionmentioning
confidence: 99%
“…6–9 The risk associated with TSH elevation and normal T4 levels is less clear, but one report has shown an association between repeated TSH elevation and poorer school performance. 10 Therefore, maintaining TSH in the normal range is widely recommended, particularly prior to three years of age, when brain development is more rapid. 2 On the other hand, overtreatment to supranormal T4 levels is also associated with adverse developmental consequences including altered temperament, 11 decreased attention and alertness, 12, 13 and decreased IQ.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of these patients requires the clinician to choose between maintaining normal serum T4 levels while permitting modest TSH elevation, or normalizing TSH at the expense of elevated serum T4. However, studies of children with congenital hypothyroidism have demonstrated that neurocognitive impairment is associated with both undertreatment (reflected by low T4 associated with elevated TSH) 6–10 and overtreatment (reflected by elevated T4). 1114 Thus, neither approach to treatment of infants who have central resistance to thyroid hormone (high T4 and high TSH) is optimal based on current data, and existing consensus recommendations offer no evidence-based guidance.…”
mentioning
confidence: 99%